Sociodemographic, clinical and obstetric profile of puerperal women in a joint accommodation: a descriptive study (Research, Society and Development, 2020)
Objective: to describe the sociodemographic, clinical and obstetric profile of puerperal women admitted to a joint accommodation. Method: a descriptive, cross-sectional study based on documentary research with 227 medical records. Data collection took place between May and October 2016 at a federal school maternity hospital. Descriptive analysis was performed for sociodemographic and clinical variables, in addition to Pearson's Chi-square and Fischer's exact tests. Results: there was an average of 2.1 pregnancies and 0.3 abortions; 97.4% postpartum women attended prenatal care, of which 79.8% attended 6 consultations. Surgical delivery predominated (51.9%), associated with diagnoses of labor and delivery, elective cesarean section, hypertensive pregnancy syndromes (p